A note on the holographic time-like entanglement entropy in Lifshitz theory - Siddhi Swarupa Jena; Subhash Mahapatra (Journal of High Energy Physics)
Abstract We explore the holographic time-like entanglement entropy (TEE) in the boundary theory of three-dimensional Lifshitz spacetime. There have been various holographic proposals for TEE in recent years and we test those proposals in the Lifshitz background. We obtain the analytic result for TEE in each proposal, compare the results, and analyze how the anisotropic scaling affects the TEE. We find that different holographic proposals give the same result for TEE in the Lifshitz background. Our analysis further suggests that the TEE of the Lifshitz system contains real and imaginary parts, both of which depend on the anisotropic parameter.